2019
DOI: 10.2478/amns.2019.2.00029
|View full text |Cite
|
Sign up to set email alerts
|

Shapley-Folkman-Lyapunov theorem and Asymmetric First price auctions

Abstract: In this paper non-convexity in economics has been revisited. Shapley-Folkman-Lyapunov theorem has been tested with the asymmetric auctions where bidders follow log-concave probability distributions (non-convex preferences). Ten standard statistical distributions have been used to describe the bidders’ behavior. In principle what is been tested is that equilibrium price can be achieved where the sum of large number non-convex sets is convex (approximately), so that optimization is possible. Convexity is thus ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Compared with the control group, patients with generalised anxiety have the proper hippocampal nerve integrity, and the plasticity marker nitrogen-acetyl aspartate (NAA) and choline complex (Cho) concentrations are significantly reduced. The Penn State University Anxiety Questionnaire (PSWQ) score was significantly negatively correlated with bilateral hippocampal NAA [12]. This study found a positive correlation between the BMI of obese children and the total score of the mental health assessment scale for obese children.…”
Section: Discussionmentioning
confidence: 59%
“…Compared with the control group, patients with generalised anxiety have the proper hippocampal nerve integrity, and the plasticity marker nitrogen-acetyl aspartate (NAA) and choline complex (Cho) concentrations are significantly reduced. The Penn State University Anxiety Questionnaire (PSWQ) score was significantly negatively correlated with bilateral hippocampal NAA [12]. This study found a positive correlation between the BMI of obese children and the total score of the mental health assessment scale for obese children.…”
Section: Discussionmentioning
confidence: 59%
“…2) Taking the load node power and voltage values of the segmented correction model at a time t  into equations ( 9) and (11), the derivative( n C  )of the state variable to time at that moment can be obtained. Assuming that after control is applied, the model is recalibrated according to the instantaneous value of the system predicted by equation ( 17), the sensitivity of the control input to n C  at time t  can be expressed as: 15), the voltage response calculation method for the segmented correction model during the prediction period is:…”
Section: Voltage Response Prediction Of Segmented Correction Modelmentioning
confidence: 99%
“…Informatisation teaching ecology is defined as the sum of the processes [3]. The research process of information-based teaching ecology and the development process of teaching application under an information technology environment reciprocate to each other.…”
Section: Relevant Research On the Strategy Of Informatisation Teaching Ecology Constructionmentioning
confidence: 99%